The Analysis of Consumer Acceptance of Starch/Tapioca Powder Made from Dried Cassava (Gaplek) with Kaporit as Whitening - Nurika, Irnia; Deoranto, Panji; Indriasari, Yuanita (Fakultas Teknologi Pertanian Universitas Brawijaya, 2008)
This study aimed at identifying variables that affected the consumer acceptance of tapioca powder made from dried cassava (gaplek). The result shows that the consumer acceptance of this product is ordinary meaning it has yet been accepted by the consumer due to its relatively high price. The fourth variable X are positively affected the variable Y which mean if the variable X increase, it will make the variable Y increase.The multiple regression model used in this research is:Y = - 13,599 + 0,855 X1 + 0,629 X2 + 0,803 X3 + 0,543 X4With R = 0,819 means the relations between all variable X to variable Y are close. R square = 0,650 means the contribution of variable X to variable Y is 65% and 35% contribution came from other variable that not include in the model. The F-test shows that F counted > F table so we can conclude that variable X affected variable Y simultaneously. The T-test shows that T counted > T table so we can conclude that variable X affected variable Y partially.Keywords : Dried cassava (Gaplek), tapioca powder, kaporit.